MURATBAY NÍZANOVTIŃ “EKI QANXOR” POVESTINDE QOLLANÍLǴAN FRAZEOLOGIZMLERDEGI ADAM MÚSHELERI ATAMALARÍNÍŃ ETIMOLOGIYASÍ - Sársenbaev, Q. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of origin and etymological meaning of the names of parts of human body in the Karakalpak language. These names have been taken not from simple sentences but from phraseological units. Examples were taken from a detective story «Ikki qanxor» by Karakalpak people’s writer M.Nizanov.
Keywords: mouth; eye; eyelashes; ear; hand; tooth